1979
DOI: 10.1177/030098587901600103
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis after Surgical Excision of Canine Melanomas

Abstract: One hundred and thirty-four dogs from which melanomas had been excised were studied until death or for at least 2 years after surgery. Seven of 49 (14%) intraoral and lip tumours and 52 of 85 (61%) skin tumours were histologically benign; in spite of this, three of seven (43%) "benign" oral and four of 52 (8%) "benign" skin lesions led to the eventual death of the host. Thirty eight of 42 (90%) dogs with a histologically malignant melanoma of the lip or oral cavity died because of the tumour but only 15 of 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
178
2
37

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(231 citation statements)
references
References 2 publications
8
178
2
37
Order By: Relevance
“…This finding is in stark contrast to previous studies, which demonstrated prognostic value associated with histologic grading. 4,5,30,31 While the results of the present study are intriguing, it is difficult to draw any conclusions from that information as this was not the focus of the present study and confounding variables are almost certainly present.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This finding is in stark contrast to previous studies, which demonstrated prognostic value associated with histologic grading. 4,5,30,31 While the results of the present study are intriguing, it is difficult to draw any conclusions from that information as this was not the focus of the present study and confounding variables are almost certainly present.…”
Section: Discussionmentioning
confidence: 68%
“…15,16 These mutations allow autophosphorylation of the receptor, independent of ligand interaction, and result in unregulated * HI 5 greater than 80% immunoreactivity (n 5 4); N 5 no immunoreactivity (n 5 34); LI 5 less than 10% immunoreactivity (n 5 8); AI 5 all immunoreactivity (n 5 12). Vet Pathol 46: 5,2009 activation. 16,23,28 Tyrosine kinase inhibitors are a targeted therapy that is being successfully utilized for GIST in people and is in clinical trials for canine MCT.…”
Section: Discussionmentioning
confidence: 99%
“…After histological diagnosis of fibrosarcoma, haemangiopericytoma, myxosarcoma or neurofibrosarcoma, all dogs that showed no clinical evidence of residual tumour or metastatic lesions immediately after surgery were followed until death or for at least three years. Post-surgical studies and statistical procedures were as previously described for dogs with melanoma [2].…”
Section: Methodsmentioning
confidence: 99%
“…52,53 Mucosal melanomas are highly metastatic and have a poor prognosis in the higher grades and stages. 54,55 As is the case for advanced melanoma in humans, melanoma in dogs is generally resistant to chemotherapy and radiation therapy, and metastasis is the major cause of treatment failure and death. 56 -58 Finally, the dog offers a good translational model because of its large size, spontaneous development of tumors, rapid assessment of therapeutic activity, and biological similarity to humans.…”
mentioning
confidence: 99%